Drafting an arbitration clause - Verdías, Marcelo (Revista de Derecho, 2017)
Entrance to an adequate arbitration is not as simply as including an arbitration clause in a contract. When parties wave its right to such an essential right as ordinary courts proceedings, they have to be extremely diligent on how they do it, and in respect to who they do it. This article provides a notion of how to avoid unwanted consequences when introducing an arbitration agreement, and how to duly anticipate contingencies in its wording. “Being the consent of the parties the main door to enter arbitration, it shall not be disregarded, neither forced”.